Efficacy of hand cooling and compression in preventing taxane-induced neuropathy: the POLAR randomized clinical trial - Michel, Laura L.; Schwarz, Daniel; Romar, Philipp; Feißt, Manuel; Hamberger, Daniel; Priester, Anastasia; Kurre, Eileen; Klein, Eva; Müller, Jana; Schinköthe, Timo; Weiler, Markus; Smetanay, Katharina; et al. (JAMA oncology, 2025)
Chemotherapy-induced peripheral neuropathy (CIPN) is a common, dose-limiting adverse effect of taxane-based chemotherapies. Currently, there is no established strategy for prevention or treatment.To compare the effectiveness of 1-sided hand cooling and compression for preventing CIPN in patients with primary breast cancer receiving taxane-based chemotherapy.The POLAR randomized clinical trial was conducted at the National Center for Tumor Diseases Heidelberg between November 2019 and January 2022. Female patients with breast cancer who received weekly nab-paclitaxel-based or paclitaxel-based neoadjuvant or adjuvant chemotherapy were enrolled. Patients with prior chemotherapy, preexisting neuropathy, or neuropathy-related comorbidities were excluded.Patients were randomized 1:1 to cooling or compression of the dominant hand. No intervention was performed on the other hand. Cooling was performed with a frozen glove and compression was applied by 2 surgical gloves (1 size smaller than the tight-fitting size) 30 minutes before, after, and during taxane administration.The primary end point was the efficacy to prevent grade 2 or higher sensory CIPN evaluated by Common Terminology Criteria for Adverse Events, version 5.0. Further CIPN assessment included the clinical version of the Total Neuropathy Score and QLQ CIPN20. CIPN rates were compared between intervention groups. Nail toxic effects, quality of life, CIPN-associated dose reductions, treatment discontinuations, and risk factors were evaluated. Follow-up examinations were performed 1 week, 1 month, and 6 to 8 months after the last taxane dose.A total of 122 female patients with primary breast cancer (mean [SD] age, 50 [12] years) were randomized to either cooling or compression of the dominant hand. Twenty-one individuals withdrew from the study, so 101 patients were included in the final analysis (n = 52 and n = 49 for cooling and compression, respectively). Both interventions significantly reduced the incidence of grade 2 or higher CIPN (cooling: 15 participants experiencing high-grade CIPN in the cooling arm [29%] vs 26 in the control arm [50%]; P = .002; effect size, 21.15% [95% CI, 5.98%-35.55%]; compression: 12 participants experiencing CIPN in the intervention arm [24%] vs 19 in the control arm [38%]; P = .008; effect size, 14.29% [95% CI, 2.02%-27.24%]). CIPN was the main reason for treatment discontinuations in 16 of 24 participants (67%). The predominant risk factors were the cumulative taxane dosage and the neurotoxic agent. Participants experiencing grade 2 or higher CIPN showed a reduced global health status during and 6 to 8 months after taxane therapy.In this randomized clinical trial, cooling and compression were highly effective and significantly reduced the risk of high-grade CIPN.ClinicalTrials.gov Identifier: NCT06541769